e+(e-7)+(e+4)+2e=82

Simple and best practice solution for e+(e-7)+(e+4)+2e=82 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for e+(e-7)+(e+4)+2e=82 equation:


Simplifying
e + (e + -7) + (e + 4) + 2e = 82

Reorder the terms:
e + (-7 + e) + (e + 4) + 2e = 82

Remove parenthesis around (-7 + e)
e + -7 + e + (e + 4) + 2e = 82

Reorder the terms:
e + -7 + e + (4 + e) + 2e = 82

Remove parenthesis around (4 + e)
e + -7 + e + 4 + e + 2e = 82

Reorder the terms:
-7 + 4 + e + e + e + 2e = 82

Combine like terms: -7 + 4 = -3
-3 + e + e + e + 2e = 82

Combine like terms: e + e = 2e
-3 + 2e + e + 2e = 82

Combine like terms: 2e + e = 3e
-3 + 3e + 2e = 82

Combine like terms: 3e + 2e = 5e
-3 + 5e = 82

Solving
-3 + 5e = 82

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 5e = 82 + 3

Combine like terms: -3 + 3 = 0
0 + 5e = 82 + 3
5e = 82 + 3

Combine like terms: 82 + 3 = 85
5e = 85

Divide each side by '5'.
e = 17

Simplifying
e = 17

See similar equations:

| 10(x+10)=16 | | -1/4b+1/5b-3=15 | | 8j+-5j+-4j+-3j-10=14 | | .6x= | | 6b+8h=140 | | 3u-2u=14 | | 3v-v-1=7 | | .5(z+3.5)=4.5 | | 6x^2+3x=15-6x^2 | | 4(3+5w)=-8 | | X+(x+1)+(x+2)=53+x | | 5j+-11j+5j=4 | | 4(2z-4)=7(z-3) | | -(y*2-2)=y*2-5-2y*2 | | 8u=8u+35 | | x^2+12x+32=4 | | 4n-12=4 | | (x+y)+(x+z)= | | 1267x=42 | | 0.38-7.45= | | 7.45-0.38= | | X*.5=2+(x+2) | | 2(7-2y)+4y=14 | | 6(4a+5)= | | 4(5x-1)=64 | | -6t+-21=-33 | | 5f-45=-65 | | 0.6(z-2)=0.4(z+7) | | logx=4.5 | | 8p+9=11+7p | | -10s+20=-23 | | -20-17q=-17q-20 |

Equations solver categories